Neuronal Differentiation of Rat Hair Follicle Stem Cells: the Involvement of the Neuroprotective Factor Seladin-1 (DHCR24) - Gilanchi, Samira (Pasteur Institute of Iran, 2014)
Background: The seladin-1 (selective Alzheimer disease indicator-1), also known as DHCR24, is a gene found to be down-regulated in brain region affected by Alzheimer disease (AD). Whereas, hair follicle stem cells (HFSC), which are affected in with neurogenic potential, it might to hypothesize that this multipotent cell compartment is the predominant source of seladin-1. Our aim was to evaluate seladin-1 gene expression in hair follicle stem cells. Methods: In this study, bulge area of male Wistar rat HFSC were cultured and then characterized with Seladin-1 immunocytochemistry and flow cytometry on days 8 to 14. Next, 9-11-day cells were evaluated for seladin-1 gene expression by real-time PCR. Results: Our results indicated that expression of the seladin-1 gene (DHCR24) on days 9, 10, and 11 may contribute to the development of HFSC. However, the expression of this gene on day 11 was more than day 10 and on 10(th) day was more than day 9. Also, we assessed HFSC on day 14 and demonstrated these cells were positive for β-ш tubulin, and seladin-1 was not expressed in this day. Conclusion: HFSC express seladin-1 and this result demonstrates that these cells might be used to cell therapy for AD in future.